2018
DOI: 10.1016/j.laa.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characterizations of anti-regular graphs

Abstract: We study the eigenvalues of the unique connected anti-regular graph A n . Using Chebyshev polynomials of the second kind, we obtain a trigonometric equation whose roots are the eigenvalues and perform elementary analysis to obtain an almost complete characterization of the eigenvalues. In particular, we show that the intervalcontains only the trivial eigenvalues λ = −1 or λ = 0, and any closed interval strictly larger than Ω will contain eigenvalues of A n for all n sufficiently large. We also obtain bounds fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…It follows that threshold graphs have no non-trivial eigenvalues in the interval (−1 − √ 2)/2, (−1 + √ 2)/2 . These results confirm two conjectures of [1] and improve the aforementioned result of [8].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…It follows that threshold graphs have no non-trivial eigenvalues in the interval (−1 − √ 2)/2, (−1 + √ 2)/2 . These results confirm two conjectures of [1] and improve the aforementioned result of [8].…”
Section: Introductionsupporting
confidence: 89%
“…In [1] it is shown that for any n, η − (A n ) < (−1 − √ 2)/2 and (−1 + √ 2)/2 < η + (A n ). This result and Theorem 6 imply the following corollary follows.…”
Section: Remarkmentioning
confidence: 99%
“…Using a similar eigenvalue interlacing technique, Corollary 4.2 was proved by E. Ghorbani [9]. The following conjecture was made in [1]. Conjecture 4.1.…”
Section: Applications In the Spectral Analysis Of Threshold Graphsmentioning
confidence: 89%
“…The graph A n is a threshold graph with binary string b = 0101 · · · 01 when n is even and b = 00101 · · · 01 when n is odd. It was proved in [18] (see also [1]) that A n has simple eigenvalues and moreover has inertia i(A 2k ) = (k, 0, k) if n = 2k is even and i(A 2k+1 ) = (k, 1, k) if n = 2k + 1 is odd. Thus, λ k+1 (A 2k+1 ) = 0 and A 2k+1 does not contain −1 as an eigenvalue.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation